2022
DOI: 10.1111/iju.14835
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and predictive model for incidence of difficult ureter during retrograde ureteroscopic lithotripsy

Abstract: Objective Difficult ureter can be a challenge for accessing upper urinary tract during lithotripsy. In this study, we evaluated the risk factors for the incidence of difficult ureter in retrograde ureteroscopic lithotripsy. Moreover, we aimed to develop a predictive model for the incidence of difficult ureter. Methods We retrospectively reviewed consecutive retrograde ureteroscopic lithotripsies performed at our institution between 2009 and 2021. A total of 1010 renal units were evaluated: 449 units with renal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 16 publications
0
8
1
Order By: Relevance
“…However, the definition of a “Difficult ureter” is still unclear. Also, the methodology to evaluate a “Difficult ureter” in these studies including the present author’s study are not fixed clearly 5 . The measurement should be unified.…”
mentioning
confidence: 91%
“…However, the definition of a “Difficult ureter” is still unclear. Also, the methodology to evaluate a “Difficult ureter” in these studies including the present author’s study are not fixed clearly 5 . The measurement should be unified.…”
mentioning
confidence: 91%
“…The result suggested that, during the treatment with retrograde intrarenal surgery, the secondary damage to the kidney is avoided and the patient's renal function is protected to the maximum. Meanwhile, flexible ureteroscopy is able to reach deeper calyces, renal pelvis and other parts, thus the overall effect of lithotripsy and clearance is better [28,29]. In terms of clinical surgical indicators, the operative time and the hospital stay of the study group were shorter than that of the control group, the intraoperative blood loss and the pain scores were significantly lower than that of control group.…”
Section: Discussionmentioning
confidence: 89%
“…Current or past stone impaction causes ureteral dilation, which may have caused the lower failure rate of UAS insertion in the stone group. In fact, we recently reported that patients with a history of stone events are less likely to require prestenting during retrograde ureteroscopic lithotripsy [ 15 ]. Additionally, younger patients, especially those in their 10s and 20s, had a higher risk for UAS insertion failure irrespective of stone events.…”
Section: Discussionmentioning
confidence: 99%